Special Event Management of Pertiwi Exhibition X Saturday Project 2024: An Evaluation of Its Implementation at Universitas Pertiwi - Frisiska Frisiska (CV. Creative Tugu Pena, 2026)
Pertiwi Exhibition X Saturday Project 2024 is an annual special event organized by Universitas Pertiwi through the collaboration between the D4 Convention and Event Management (MICE) Study Program and the Visual Communication Design (DKV) Study Program. The event was designed to provide a platform for young people to express themselves freely through the integration of fashion, beauty, art, and music. To accomplish this objective, the organizers presented an exhibition featuring students’ design works, ten booths displaying new and trendy products, thirteen food and beverage booths, and a live performance by the indie band MANEROLE. This study adopted Joe Goldblatt’s Special Event Management Process as its conceptual framework, which consists of five stages: research, design, planning, coordination, and evaluation. A qualitative approach employing an evaluative method was used to assess the implementation of the event by comparing it with the previous editions held in 2022 and 2023. The research stage involved interviews and focus group discussions with youth communities to identify their entertainment preferences. The planning stage focused on event preparation, while the coordination stage emphasized communication among the MICE organizing committee, the DKV team, the supervising lecturer, and the Student Executive Board (BEM). The evaluation stage identified the strengths and challenges encountered during the event implementation and was supported by a SWOT analysis of the overall special event management process. The evaluation, based on Dunn’s five criteria—effectiveness, adequacy, implementation, responsiveness, and appropriateness—revealed that the event strategy shifted from a talent competition format to an exhibition and bazaar concept. Nevertheless, challenges related to achieving visitor targets and exhibitor satisfaction continued to recur throughout all three editions of the event.